Sex and the Sailor: Sexual Violence at Sea in the Early Modern British World, c. 1600–c. 1750 - Murphy, Elaine (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2025)
A sea voyage in the early modern period came with many inherent risks and often considerable unpleasantness for travellers ranging from storms and shipwreck to seasickness. But not all those who voyaged across water were in the same boat, as it were. Women and young boys faced additional dangers of unwanted sexual attention or rape from predators on their ships or those they encountered, such as pirates or enemy warships. This article examines the experiences and vulnerability of women and young boys as they dealt with the threat of sexual assault when they journeyed by sea.